Adolescents' Perceptions of Their School Counselors' Impact. Issue 1 (2nd January 2016) - Ohrt, Jonathan H.; Limberg, Dodie; Bordonada, Tiffany M.; Griffith, Catherine; Sherrell, Renee S.
Abstract : School counselors focus on students' academic, career, and social/emotional needs in addition to fulfilling various administrative expectations. In this article, we explored adolescents' perceptions of their school counselors' impact. We used thematic analysis to analyze 273 students' essays about how their school counselors affected them and identified eight themes: (a) College and Career Readiness, (b) Life Skills, (c) Multiple Roles, (d) Individual Attention, (e) Emotional/Social Support, (f) Therapeutic Relationship, (g) Advocacy, and (h) Academic Achievement. We discuss implications and suggestions for future research.